Gemistocytic tumor cells programmed for glial scarring characterize T cell confinement in IDH-mutant astrocytoma - Levi van Hijfte; Marjolein Geurts; Iris de Heer; Santoesha A. Ghisai; Hayri E. Balcioglu; Youri Hoogstrate; Wies R. Vallentgoed; Rania Head; Rosa Luning; Thierry van den Bosch; Bart Westerman; Pieter Wesseling; et al. (Nature Communications)
Abstract Isocitrate dehydrogenase 1/2 mutant (IDHmt) astrocytoma is considered a T cell-deprived tumor, yet little is known regarding the phenotypes underlying T cell exclusion. Using bulk, single nucleus and spatial RNA and protein profiling, we demonstrate that a distinct spatial organization underlies T cell confinement to the perivascular space (T cell cuff) in IDHmt astrocytoma. T cell cuffs are uniquely characterized by a high abundance of gemistocytic tumor cells (GTC) in the surrounding stroma. Integrative analysis shows that GTC-high tumors are enriched for lymphocytes and tumor associated macrophages (TAM) and express immune cell migration and activation programs. Specifically, GTCs constitute a distinct sub-cluster of the astrocyte-like tumor cell state that co-localizes with immune reactive TAMs. Neighboring GTCs and TAMs express receptor-ligand pairs characteristic of reactive astrogliosis and glial scarring, such as SPP1/CD44 and IL-1β/IL1R1. Collectively, we reveal that T cell confinement in IDHmt astrocytomas associates with GTC-TAM networks that mimic glial scarring mechanisms.